Variasi Pengaturan Tempat Duduk: Upaya Peningkatan Konsentrasi Belajar Siswa - Silfy Nur Afifah; Prima Priscilla Putri W; Qatrunnada Arraudah Hanad (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
Learning concentration is a student's ability to focus on learning, which affects understanding and learning success. An important factor that influences it is the seating arrangement in the classroom. Research shows that the right seating arrangement can improve students' concentration, engagement and creativity, especially in Arabic language learning. This research uses a systematic literature review (SLR) approach to systematically review relevant literature. A good seating arrangement creates a conducive learning environment, improving students' concentration, motivation and achievement. Variations in arrangement, such as U-formation, strengthen connections between students and increase teacher attention. This helps students avoid boredom, increases interaction, and makes it easier to manage the class and deliver material, which has a positive impact on academic outcomes. Classroom seating arrangements are important for creating a comfortable and conducive learning environment. Variations in seating arrangements improve concentration, reduce boredom and provide a more enjoyable learning experience. For teachers, it makes it easier to manage the class, increase interaction and attention to students, which has a positive impact on student motivation and achievement.